Phytoplankton Diversity as Bioindicator of Pollution in Jenes River, Surakarta - Endah Pratiwi; Dhiya' Choirunnisa; Riannisa Shafira; Alanindra Saputra (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractThis research aims to identify the types of phytoplankton, identify the abundance of phytoplankton, and study the relationship between environmental factors and the abundance of phytoplankton. This research was carried out on January 10, 2023, at the Jenes River, Surakarta. Sampling was carried out at 3 observation stations to identify environmental factors (pH, DO, CO2, salinity, BOD, light intensity, temperature, and brightness). Observations were carried out at three stations, namely upstream, middle and downstream, namely, in the morning (06.00–07.00 WIB) and during the day (12.00–14.00 WIB). Measurements of environmental factors were carried out at the integrated laboratory at Sebelas Maret University, Surakarta. The results of the research showed that the phytoplankton found were 9 families consisting of 11 species with an average abundance of 6,834 individuals/L in the morning day and an average abundance of 13,088 individuals/L during the day. The most abundant phytoplankton in the morning observations was Ulothrix sp. Meanwhile, the most abundant phytoplankton in the afternoon observations was Chroococcus sp. This abundance is also influenced by environmental factors such as pH, DO, Salinity, BOD, CO2, and temperature. The research found that the middle station had the highest phytoplankton diversity index during the day (1.6), possibly because it was indicated to be lightly polluted, allowing the life of many phytoplankton such as Closterium sp. and Quadrigula sp. The highest abundance of phytoplankton in the morning is Ulothrix sp., in the afternoon, it is Chroococcus sp.AbstrakPenelitian ini bertujuan untuk mengidentifikasikan jenis fitoplankton, kelimpahan fitoplankton, dan analisis hubungan faktor lingkungan dengan kelimpahan fitoplankton di Sungai Jenes Surakarta. Penelitian ini dilaksanakan pada 10 Januari 2023 di Sungai Jenes, Surakarta. Pengambilan sampel dilakukan di 3 stasiun pengamatan untuk mengukur faktor lingkungan (pH, DO, CO2, salinitas, BOD, intensitas cahaya, suhu, dan kecerahan). Pengamatan dilakukan di tiga stasiun yaitu hulu, tengah dan hilir sebanyak 2 yaitu, pagi hari (06.00–07.00 WIB) dan siang hari (12.00–14.00 WIB). Pengujian faktor lingkungan dilakukan di laboratorium terpadu Universitas Sebelas Maret, Surakarta. Hasil penelitian menunjukkan bahwa fitoplankton ditemukan berjumlah 9 famili terdiri dari 11 spesies dengan rata-rata kelimpahan 6.834 individu/L pagi hari dan rata rata kelimpahan 13.088 individu/L pada siang hari. Fitoplankton yang paling melimpah pada pengamatan pagi hari adalah Ulothrix sp., sedangkan siang hari adalah Chroococcus sp. Kelimpahan ini juga dipengaruhi oleh faktor lingkungan seperti pH, DO, Salinitas, BOD, CO2 , dan suhu. Penelitian menemukan bahwa stasiun tengah memiliki indeks keanekaragaman fitoplankton tertinggi pada siang hari (1,6), kemungkinan karena terindikasi tercemar ringan, memungkinkan hidupnya banyak fitoplankton seperti Closterium sp. dan Quadrigula sp. Kelimpahan fitoplankton tertinggi pada pagi hari adalah Ulothrix sp., sementara pada sore hari adalah Chroococcus sp.